Cárcel de amor: an Example of Narrative Discursive Epistolary Structure in the Imaginative Creation of the Sentimental Novel (Castilla. Estudios de Literatura, 2013)
In this work we have examined the different types of inserted texts in Cárcel de amor in order to fix his action in the set of the novel. The artistic singularity of the work selected undoubtedly relates to the thematic and structural variety of the letters and of the speeches, with the capacity of the author to find the thoughts, arguments and suitable affections to each of them.